Endoscopic resection techniques for squamous premalignant lesions and early carcinoma of the esophagus: ER-Cap, MBM, and ESD, how do we choose? A multicenter experience. (March 2020) - Yu, Xinying; Chen, Jian; Yuan, Zhiqiang; Liu, Hui; Liu, Fugang; Liu, Yong; Xue, Liyan; He, Shun; Zhang, Yueming; Dou, Lizhou; Liu, Xiao; Zhao, Deli; et al.
Background: Endoscopic resection cap technique (ER-Cap), multiband mucosectomy (MBM), and endoscopic submucosal dissection (ESD) have been widely applied in the treatment of esophageal squamous neoplasia and cancer. However, little is known with regards to the comparison of these methods. This study aimed to compare the feasibility, safety, effectiveness, and costs of these three techniques. Methods: A retrospective analysis of patients with squamous premalignant or early malignant lesions of the esophagus undergoing ER-Cap, MBM, or ESD from January 2009 to December 2015 in one of the centers in China was performed. The procedural data and follow-up data for all patients were recorded. Results: A total of 672 patients with 733 lesions were included; 148 lesions (133 patients) were treated with ER-Cap, 427 lesions (388 patients) with MBM, and 158 lesions (151 patients) with ESD. The mean age was 61.59 years and the male-to-female ratio was 2.78:1. The operation time was significantly shorter for ER-Cap (29.26 ± 16.73 mins, p < 0.001) group, and the hospitalization costs were significantly lower in the MBM group (20, 942.03 ± 8435.56￥, p = 0.003). The resection sample size of ESD was significantly larger (4.40 ± 1.20 cm, p < 0.001) and the en bloc resection rate of ESD was significantly higher ( p < 0.001) than that of the other two groups. The frequencies of perforation, bleeding, and cicatricial stenosis were significantly lower in the MBM group ( p < 0.001, p = 0.011, p = 0.009). Three local recurrences were observed in the ER-Cap group, while no recurrence was observed in MBM and ESD groups. There were three and two metastatic patients observed in the MBM and ESD groups, respectively. Conclusions: ER-Cap, MBM, and ESD are all minimally invasive, safe, and effective methods for treating early esophageal squamous cell carcinoma. MBM could be considered as a good alternative when performed by a less-experienced endoscopist in high-incidence areas with limited resources.